Value Chain of Eri Cocoon Production to Innovative Product from Eri Pupae in Thap Sadet District, Sa Kaeo Province, Thailand - Chainam, Jarunan; Pimpo, Pannee; Sangsawad, Papungkorn; Somsaang, Chaiwat; Yongphet, Piyaphong (Area Based Development Research Journal, 2025)
Thap Sadet Subdistrict in Ta Phraya District, Sa Kaeo Province, Thailand, is a border community where agriculture is the main occupation. Eri silkworm farming is practiced as a supplementary livelihood during the agricultural off-season. Farmers in four villages cultivate Eri silkworms, yielding an average of 20–30 kilograms of fresh cocoons per production cycle. However, the community faces persistent challenges including the production of small, low-quality cocoons, a shortage of Eri silkworm eggs, inconsistent yields, and limited market access for Eri pupae. To address these challenges, a multi-faceted community development project was implemented with five strategic components: 1) Sustainable Community Group Formation: A participatory forum was organized with local stakeholders, including community leaders and the Ta Phraya District Community Development Office, to identify needs and formulate a strategic plan for sustainable development. 2) Supply Chain and Production Process Management: A comprehensive approach was adopted to improve the Eri silkworm farming value chain, from breeding to final products. 3) Learning and Product Development: Through food processing technologies, value-added products such as dried Eri pupae noodles, rice seasoning powder, and Eri pupae chocolate were developed. Organic liquid fertilizers and zero-turn composts were also created from silkworm waste. Product packaging was enhanced, and a community enterprise group was registered. 4) Marketing and Network Promotion: Partnerships with the Sa Kaeo Sericulture Promotion Center enabled market linkages. Training in branding, e-commerce, and participation in trade fairs expanded both online and offline sales channels. 5) Partnership and Community Collaboration: Continuous support from partner organizations fostered knowledge-sharing, innovation, and sustainable community development. Farmers gained expertise in Eri silkworm breeding and processing, producing golden-colored cocoons that met Grade A standards. The newly bred Sa Kaeo Tapioca Eri Silkworm was registered with the Department of Sericulture. Further developments included simplified methods for egg production and breeding, helping reduce dependency on external sources. Farmers adopted innovative feeding techniques—replacing whole-cassava stem feeding with small-branch feeding—to optimize space, ensure uniform worm growth, and improve cocoon quality. Cassava leaf preservation methods were also introduced to prolong freshness and ensure a consistent food supply. Training sessions and collaborations with nearby sericulture groups enabled the integration of six breeding cycles from three different silkworm strains, under technical guidance from the Sa Kaeo Sericulture Promotion Unit. Additionally, semi-patented food products such as Eri pupae noodles were created, increasing monthly household income from an average of 2,000 Baht (61 USD) to 5,000–6,000 Baht (153–184 USD). The revenue from dried noodle sales alone added approximately 2,000 Baht (61 USD) monthly per household. Silkworm waste was used to produce organic fertilizers, contributing to a zero-waste model and creating supplementary income. Eri cocoon waste was also developed into sericin extract for potential use in cosmetic products, opening doors to new markets in the beauty industry. The establishment of the Thap Sadet Eri Silkworm Farming and Processing Community Enterprise Group and a learning center in Ban Thap Seree created long-term support infrastructure. The community now belongs to the provincial Eri silkworm network, allowing better access to knowledge, funding, and trade opportunities. This initiative transformed the local community through skill development in silkworm breeding, integrated farming, product processing, and sustainable waste utilization. Farmers achieved standard-compliant cocoon production, developed breeding techniques for golden cocoons, and adopted eco-friendly farming practices. A silkworm egg bank was established to preserve genetic diversity and prevent inbreeding. Community innovators emerged as local trainers and knowledge disseminators. With sustained institutional support and increased community participation, this model presents a replicable approach to rural economic empowerment, capacity building, and sustainable agro-industrial development in Thailand.